Implementing Assessment literacy in ESL/EFL at Undergraduate Level in Bangladeshi Universities: Imperativeness and Challenges - Protiva Rani Karmaker (Journal of English Education and Teaching, 2020)
The paper concentrates on investigating the implementation of assessment literacy at the tertiary level of Bangladesh. It also tries to explore the existing challenges which the teachers face in ELT classroom while implementing effective assessment techniques in evaluating academic examination scripts. In this regard, a survey method involving a questionnaire survey was used to obtain a quantitative insight of the study. After studying the responses from 10 respondents of two public universities of Bangladesh, the researcher attained the findings that demonstrated respondents’ experience and suggestions regarding assessment literacy in English language teaching at undergraduate level in the respective university, which include a number of barriers, like lack of training in achieving assessment literacy, insufficient support from the university, and disparity between learning objectives and assessment techniques. To ensure bonafide assessment literacy, the findings also provided some feasible suggestions, like offering students an opportunity to convert test into learning experiences, ensuring appropriate math between assessment and learner ability and regulating self-assessment on regular basis.